The Critical Thinking Analysis of Middle School Students in Solving Open Ended Mathematical Problems at Social Arithmetic Material - Tri Novita Irawati (Universitas Islam Jember, 2017)
The ability to think critically is a thinking skill used to systematically investigate one's thinking process in using evidence and logic to the thinking process. This capability can be developed through the application of open ended problems. This type of research is qualitative. The research approach used is case study. Analysis of research data using the method of observation, test, and interview. In addition, validity and reliability tests were conducted on the instruments used. Based on the results of the validation level analysis for all aspects of 0.9 with high interpretation. The level of reliability of the test questions reached a high level with a coefficient of 0.92. The critical thinking ability of junior high school students in solving the problem of open ended problem math on the material of social arithmetic is still low reaching 50%. While the result of critical thinking ability analysis on each indicator is ability to give simple explanation 27%, build basic skill 24%, conclusion 18% make further explanation 10% and strategy and tactics reach 21%. Based on the above, there needs to be an alternative solution in improving students' critical thinking skills through the application of open ended problem in every learning mathematics.Keywords: Critical thinking ability, open ended problem